2019
DOI: 10.3390/su11041058
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Factors and Sustainable Performance Measurement (SPM) Practices of Malaysian Electronics and Electrical Companies

Abstract: In the present world, there is a rapidly growing level of awareness of social and environmental activities. Consequently, a company’s profile is not substantiated purely in relation to financial issues, rather, a need for the inclusion of environmental and social perspectives arises. This is known as sustainable performance. Hence, there is a persistent need for the practice of sustainable performance measurements (SPMs). However, despite the implementation of sustainable performance in developed climes like E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The financial variables are the most dominant factors for accessing a firm's sustainable performance; alterations in these factors can transform the performance of companies [21,22].…”
Section: Financial and Economic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The financial variables are the most dominant factors for accessing a firm's sustainable performance; alterations in these factors can transform the performance of companies [21,22].…”
Section: Financial and Economic Performancementioning
confidence: 99%
“…The financial variables are the most dominant factors for accessing a firm's sustainable performance; alterations in these factors can transform the performance of companies [21,22]. Organizations select their own specific factors to estimate the quality of performance based on their financial statements [20].…”
Section: Financial and Economic Performancementioning
confidence: 99%
“…This satisfies the findings stated in their article that to be a sustainable business it is mandatory to have some measures which will prove the business sustainable. Similar studies are also found to investigate Sustainable Performance Measurement (SPM) in electrical and electronics companies [69] and mandatory measures to prove business sustainable [70].…”
Section: (D) Practical Significancementioning
confidence: 91%
“…For example, Si et al (2020) employ factor analysis to investigate the interactive endogeneity relationship between RandD investment and financial sustainability performance and the moderate effect of executive incentives. Ong et al (2019) conduct a selfadministered questionnaire survey of 217 electrical and electronics companies and a hypotheses test through structural equation modelling (SEM) to identify critical success factors for sustainable performance measurement in Malaysian electrical and electronics companies. Yang et al (2017) posit a new hybrid evaluation index system from sustainability and internal group management perspectives.…”
Section: Methodsmentioning
confidence: 99%